Klasifikasi Sentimen Opini Pada Aplikasi Guitar Tuner - Dachi, Christian Moris; Berutu, Sunneng Sandino; Jatmika, Jatmika (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
Current technological advances have an impact on various fields, including music applications. Guitar Tuna and other popular music applications can have an impact on public perception, customer decisions, and company reputation. This study analyzes user sentiment for Guitar Tuna using the Naive Bayes and Support Vector Machine (SVM) algorithms. Play Store is the place where data is obtained consisting of 626 neutral reviews, 234 positive reviews, and 2 negative reviews that have gone through several stages, namely preprocessing, classification, labeling, crawling, and evaluation models. The analysis resulted in a Naive Bayes accuracy of 0.95 and SVM of 0.97. The results of the Naive Bayes classification showed the highest value in the neutral sentiment precision parameter of 0.94. In the (SVM) method, positive sentiment gets the highest value at a precision of 1, while the highest recal and f1-score values are achieved by neutral sentiment with values 1 and 0.98 in the SVM method.Keywords: Naïve Bayes; Support Vector Machine; Sentiment Classification; Opinion Analysis; Guitar Tuna.                                                                      AbstrakKemajuan teknologi saat ini berdampak pada berbagai bidang, termasuk aplikasi musik. Guitar Tuna dan aplikasi musik populer lainnya dapat berdampak pada persepsi publik, keputusan pelanggan, dan reputasi perusahaan. Studi ini menganalisis sentimen pengguna untuk Guitar Tuna dengan menggunakan algoritma Naive Bayes dan Support Vector Machine (SVM). Play Store ialah tempat perolehan data terdiri dari 626 ulasan netral, 234 ulasan positif, dan 2 ulasan negatif yang sudah melakukan sejumlah tahapan yakni preprocessing, classification, labeling, crawling, serta evaluation model. Penganalisisan tersebut menghasilkan akurasi Naive Bayes sebesar 0,95 dan SVM sebesar 0,97. Hasil klasifikasi Naive Bayes menunjukan nilai tertinggi pada parameter precision sentimen netral sebesar 0,94. Pada metode (SVM), sentimen positif mendapatkan nilai tertinggi pada precision sebesar 1, sedangkan nilai tertinggi recal dan f1-score dicapai sentimen netral dengan nilai 1 dan 0.98 pada metode SVM.